2017
DOI: 10.1093/bib/bbx164
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis and prediction of type IV secreted effector proteins by machine learning approaches

Abstract: In the course of infecting their hosts, pathogenic bacteria secrete numerous effectors, namely, bacterial proteins that pervert host cell biology. Many Gram-negative bacteria, including context-dependent human pathogens, use a type IV secretion system (T4SS) to translocate effectors directly into the cytosol of host cells. Various type IV secreted effectors (T4SEs) have been experimentally validated to play crucial roles in virulence by manipulating host cell gene expression and other processes. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 86 publications
(114 reference statements)
3
58
1
Order By: Relevance
“…In our previous study (17), we found that Nomogrambased model gave better forecast accuracy results for CI-AKI in AMI patients, as compared to Mehran risk scores. Similar to the previous studies (17)(18)(19), our new data shows that machine learning models are superior to traditional logistic regression for developing predictive models. This finding makes sense because machine learning models are capable of learning complex discriminative features from large volumes of data without assumption of linearity.…”
Section: Discussionsupporting
confidence: 84%
“…In our previous study (17), we found that Nomogrambased model gave better forecast accuracy results for CI-AKI in AMI patients, as compared to Mehran risk scores. Similar to the previous studies (17)(18)(19), our new data shows that machine learning models are superior to traditional logistic regression for developing predictive models. This finding makes sense because machine learning models are capable of learning complex discriminative features from large volumes of data without assumption of linearity.…”
Section: Discussionsupporting
confidence: 84%
“…The evolutionary data in the form of Position-Specific Scoring Matrix (PSSM) profile are informative and have proved useful in a number of biological classification problems [28,[33][34][35][36][37][38][39][40][41][42][43][44][45]. In this work, the PSSM profile was generated by running PSI-BLAST against the uniref50 database with the parameters j = 3 and h = 0.001.…”
Section: Position-specific Scoring Matrix Based Transformation (Pssm)mentioning
confidence: 99%
“…As one of the most widely used ML algorithms applied to classification problems [11,13,14,28,35,37,39,42,53], SVM [54] maps the input data into a high-dimensional space through the use of kernel functions and finds a hyperplane that maximizes the distance between the hyperplane and two types of samples. By mapping the unseen samples into the same space, SVM can predict the new samples based on which side of the hyperplane they fall in.…”
Section: Support Vector Machinementioning
confidence: 99%
“…To make a fair comparison, the same independent data set, which consists of 20 T4SEs and 139 non-T4SEs, was used for all models. Among these machine learning-based methods, the results showed that our T4SE-XGB model achieved the overall best performance with an ACC of 97.48%, F-value of 90.48% and MCC of 0.8916, followed by the state-of-the-art machine learning model called Bastion4 (Wang J. et al, 2019), which achieved 96.23% on ACC, 86.96% on F-value and 0.8579 on MCC. Moreover, the T4SE-XGB trained by fewer training samples also gets more stable prediction performance than the deep learningbased method named CNN-T4SE (VOTE 2/3), which takes the majority votes of the three best-performing convolutional neural network-based models (CNN-PSSM, CNNPSSSA, and CNN-Onehot).…”
Section: Comparison With Other Classification Algorithms and Existingmentioning
confidence: 99%